2014
DOI: 10.1038/sc.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysreflexia during bowel evacuation procedures and bladder filling in subjects with spinal cord injury

Abstract: Study design: Randomized, controlled clinical trial. Objectives: Bladder and bowel management may cause serious autonomic dysreflexia (AD) in subjects with high spinal cord injury (SCI). We aimed at investigating autonomic responses to digital rectal evacuation (DE), transanal irrigation (TAI) with 500 ml and filling cystometry (FC) in SCI. Setting: Aarhus University Hospital, Denmark. Methods: Eight subjects with SCI (AIS A) at or above T6 (high SCI) and a previous history of AD were compared with three subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 21 publications
1
29
0
4
Order By: Relevance
“…Of the studies reviewed, the majority were preinterventionpostintervention comparisons or were of limited sample size (n = 8-26). [37][38][39][40][41]43,44 In an effort to increase evidence-based practice in this area, it is suggested in future studies to perform randomized controlled trials with an appropriate sample size and include cervical/thoracic, complete/incomplete SCI individuals. Although a variety of medications were used in the treatment of hypertension or during a hypertensive crisis, nifedipine in particular was shown to be the most effective during urodynamics, 39 cystoscopy 47 and ESWL 58 both for relief of acute AD and for the prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies reviewed, the majority were preinterventionpostintervention comparisons or were of limited sample size (n = 8-26). [37][38][39][40][41]43,44 In an effort to increase evidence-based practice in this area, it is suggested in future studies to perform randomized controlled trials with an appropriate sample size and include cervical/thoracic, complete/incomplete SCI individuals. Although a variety of medications were used in the treatment of hypertension or during a hypertensive crisis, nifedipine in particular was shown to be the most effective during urodynamics, 39 cystoscopy 47 and ESWL 58 both for relief of acute AD and for the prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 34 reported that during cystoscopy SCI individuals developed greater changes in SBP than urodynamics (67.1 ± 33.8 vs 51.8 ± 21.8 mm Hg), indicating that stimulation of the urethra/prostate/internal sphincter region probably is a more potent stimulus of AD than just the filling of the bladder. Faaborg et al 44 showed that SBP increased less during transanal irrigation (36 mm Hg, range 30-63) than during digital evacuation (57 mm Hg, range 41-75) or filling cystometry (61 mm Hg, range 55-100)-the SBP response between digital evacuation and filling cystometry was insignificant.…”
Section: Urodynamics and Cystometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Digital anorectal stimulation, rectal evacuation or transanal irrigation may cause autonomic dysreflexia either with symptoms or as silent autonomic dysreflexia. 17 For children, fussiness and irritability are common signs that autonomic dysreflexia may be present. 18 This variable is new in the data set but part of the NBD score.…”
Section: Uneasiness Headache or Perspiration During Defecationmentioning
confidence: 99%
“…There was agreement early in the discussion that many serious health issues and potential incontinence "accidents" could be avoided if sensory information, such as bladder fullness, pain due to impaction or urinary tract infection (UTI) was available. For example, it is well documented that autonomic dysreflexia can be triggered by activation of the sensory afferents due to an over-filled bladder or colon, routine bladder emptying, digital stimulation or the process of manual evacuation (Faaborg et al, 2014;Lee et al, 2017;Vaidyanathan et al, 2017Vaidyanathan et al, , 2018. Dysfunction in sensory feedback varies based on each injury; while some individuals with SCI retain some sensation, others have little or no sensory warning before a bowel or bladder movement.…”
Section: Sensory Awarenessmentioning
confidence: 99%